DEAD-box RNA helicase 10 is required for 18S rRNA maturation by controlling the release of U3 snoRNA from pre-rRNA in embryonic stem cells - Xiuqin Wang; Gongcheng Hu; Lisha Wang; Yuli Lu; Yanjiang Liu; Shengxiong Yang; Junzhi Liao; Qian Zhao; Qiuling Huang; Wentao Wang; Wenjing Guo; Heying Li; et al. (Nature Communications, 2024)
Abstract Ribosome biogenesis plays a pivotal role in maintaining stem cell homeostasis, yet the precise regulatory mechanisms governing this process in mouse embryonic stem cells (mESCs) remain largely unknown. In this investigation, we ascertain that DEAD-box RNA helicase 10 (DDX10) is indispensable for upholding cellular homeostasis and the viability of mESCs. Positioned predominantly at the nucleolar dense fibrillar component (DFC) and granular component (GC), DDX10 predominantly binds to 45S ribosomal RNA (rRNA) and orchestrates ribosome biogenesis. Degradation of DDX10 prevents the release of U3 snoRNA from pre-rRNA, leading to perturbed pre-rRNA processing and compromised maturation of the 18S rRNA, thereby disrupting the biogenesis of the small ribosomal subunit. Moreover, DDX10 participates in the process of liquid-liquid phase separation (LLPS), which is necessary for efficient ribosome biogenesis. Notably, the NUP98-DDX10 fusion associated with acute myelocytic leukemia (AML) alters the cellular localization of DDX10 and results in loss of ability to regulate pre-rRNA processing. Collectively, this study reveals the critical role of DDX10 as a pivotal regulator of ribosome biogenesis in mESCs.